2013
DOI: 10.1007/s10886-013-0339-3
|View full text |Cite
|
Sign up to set email alerts
|

Communication Disruption of Guava Moth (Coscinoptycha improbana) Using a Pheromone Analog Based on Chain Length

Abstract: The guava moth, Coscinoptycha improbana, an Australian species that infests fruit crops in commercial and home orchards, was first detected in New Zealand in 1997. A four-component pheromone blend was identified but is not yet commercially available. Using single sensillum recordings from male antennae, we established that the same olfactory receptor neurons responded to two guava moth sex pheromone components, (Z)-11-octadecen-8-one and (Z)-12-nonadecen-9-one, and to a chain length analog, (Z)-13-eicosen-10-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The analysis of the unusual features of the CcapOBP22 binding pocket will also be useful for future structure-based design, for in silico ligand identification as well as optimization of chemical scaffolds that can be exploited as new tools to interfere with medfly olfaction (Carey and Carlson, 2011;Suckling et al, 2013;Pelosi et al, 2014), or to improve the efficacy of trapping systems (Tan et al, 2014). Given its sequence divergence from other OBPs characterized using structural biology, the molecular structure of CcapOBP22 will be a useful starting point to investigate the molecular architecture of the numerous as-yet-uncharacterized OBP molecules from C. capitata and from other insects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the unusual features of the CcapOBP22 binding pocket will also be useful for future structure-based design, for in silico ligand identification as well as optimization of chemical scaffolds that can be exploited as new tools to interfere with medfly olfaction (Carey and Carlson, 2011;Suckling et al, 2013;Pelosi et al, 2014), or to improve the efficacy of trapping systems (Tan et al, 2014). Given its sequence divergence from other OBPs characterized using structural biology, the molecular structure of CcapOBP22 will be a useful starting point to investigate the molecular architecture of the numerous as-yet-uncharacterized OBP molecules from C. capitata and from other insects.…”
Section: Discussionmentioning
confidence: 99%
“…Given its sequence divergence from other OBPs characterized using structural biology, the molecular structure of CcapOBP22 will be a useful starting point to investigate the molecular architecture of the numerous as-yet-uncharacterized OBP molecules from C. capitata and from other insects. The analysis of the unusual features of the CcapOBP22 binding pocket will also be useful for future structure-based design, for in silico ligand identification as well as optimization of chemical scaffolds that can be exploited as new tools to interfere with medfly olfaction (Carey and Carlson, 2011;Suckling et al, 2013;Pelosi et al, 2014), or to improve the efficacy of trapping systems (Tan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…9 For the carposinid moths, Suckling et al investigated chain length variants using the peach fruit moth pheromone to disrupt guava moth. 10 More recently, Twidle et al have shown that the ester analogue (Z)-heptyl undec-4-enoate has an inhibitory effect on raspberry bud moth, 11 similar to that of the formate analogues of Type I aldehyde pheromones. 12 The aim of this work was to build on that knowledge and investigate changes directly to the carbonyl group of (7Z)-alken-11-ones of the carposinids, focusing on (Z)-nonadec-12-en-9-one (1) (or as it is historically known, (7Z)-nonadecen-11-one) which is common to the three known carposinid pheromone blends.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Rigorous degassing of the solvents reduced the unwanted disulfide formation, allowing the target compound (Z)-dec-3-enyl(octyl)sulfane ( 9) to be produced with a satisfactory yield of 54%. The final step of the synthesis was the oxidation of the thioether (9) to the target sulfoxide (Z)-1-(octylsulfinyl)-dec-3-ene (10). This was achieved using the TeO 2 −H 2 O 2 system of Kwan et al, 15 giving the sulfoxide (10) in 87% yield.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation